The effects of acute and chronic exercise on immune markers of TH1/TH2 cells in older adults: a systematic review - Teodoro, Thiago Henrique; Costa, Katerine Palharini Manfrin; Prestes, Jonato; Campanholi, José; Navalta, James; Pereira, Guilherme Borges (Frontiers in Physiology, 2025)
PurposeImbalance between Th1 and Th2 cells correlated with increased disease incidence, is well-documented in the older adult. Both acute and chronic exercise induce a transient shift in organic homeostasis, modulating the immune system and impacting the balance between Th1 and Th2 cells. This review investigates the impact of acute and chronic exercise on immune markers of Th1 and Th2 cells in the older adults.MethodsThis study was conducted as a systematic review, following PRISMA guidelines, databases including PubMed, Web of Science, Embase, Science Direct, and Scopus were searched until March 2024, identifying randomized controlled trials and prospective observational studies that examined the effects of acute and chronic exercise on intracellular and surface markers, cytokines, and immunoglobulins in older adults. Studies involving animal subjects, isolated cells, diseased patients, or exposure to medications and drugs were excluded. The quality of the selected studies was assessed using the Cochrane risk of bias tool (ROB2), with data organized and presented in tables and figures.ResultsFourteen studies with 525 participants were included in the analysis. An acute session significantly increased serum IL-4, IL-6, and IL-10 levels immediately afterward, returning to baseline within 1 hour at moderate to high intensities. Chronic exercise at moderate to high intensities reduced serum TNF-α, IL-6, and the CD4/CD8 ratio, while increasing IL-10 levels after 24 weeks. Intracellular, other surface markers and cytokines, and immunoglobulins were not analyzed.ConclusionChronic exercise decreases serum TNF-α and IL-6 levels, lowers the CD4/CD8 ratio, and increases IL-10 after 24 weeks, aiding Th1 and Th2 balance. Acute exercise temporarily increases serum IL-4, IL-6, and IL-10 levels, returning to baseline within an hour, indicating short-term immune modulation of Th1/Th2 balance.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021244426, Identifier CRD42021244426.